Estimation of sea level rise in Kota Kinabalu - Looi, Kai Xiang (2015)
"The increasingly rising trend of sea level is an issue that raise global considerable concern. Due to the limited data and research available in this area, the study will carried out to estimate the sea level rise in Kota Kinabalu by using correlation analysis. The estimation of sea level rise upon the coastal plain of Kota Kinabalu Sabah are examined by identifying the trend analysis of tide gauge pattern, preCipitation pattern and temperature within the range of 10 years data, from 2005- 2014. The rate of sea level rise for the study area was estimated at an annual rise of 9.172 mm/year for the past 10 years. By the year of 2100, the sea level is projected to be rise by an additional of 0.789 m in Kota Kinabalu based on the linear equation obtained from annual sea level rise trend. The changes in percentage of sea level, temperature and preCipitation in Kota Kinabalu for the past 10 years are also calculated to show their changes as compared to last year to have a better understanding on their fluctuation of values. Correlation of the relationship between sea level, temperature and preCipitation are considered weak and insignificant. Responding to sea level rise in the most economically efficient manner will challenge humans to learn and adapt over a long period of time.